2022-RA-889-ESGO The vaginal microbiota composition is associated with severity of cervical dysplasia. (20th October 2022) - Norenhag, Johanna; Edfeldt, Gabriella; Du, Juan; Stålberg, Karin; Garcia, Fabricio; Hugerth, Luisa Warchavchik; Engstrand, Lars; Koistinen, Ina Schuppe; Fransson, Emma; Olovsson, Matts
Abstract : Introduction/Background: Certain compositions of vaginal microbiota, and specific bacterial species, seem to be associated with HPV infection and the subsequent development of cervical dysplasia and cancer. In order to better understand the association between vaginal microbiota, HPV-infection and dysplasia, we performed shotgun metagenomic sequencing to taxonomically and functionally characterize the composition of the vaginal microbiota of women with and without cervical dysplasia. The HPV status for all study persons was also analysed. Methodology: Women with histologically verified cervical dysplasia (n = 161; low grade dysplasia (LSIL) n=73, high-grade dysplasia (HSIL) n= 88) were recruited at Uppsala University hospital, Sweden. Women with two normal consecutive cervical screening tests were included as controls (n= 175) Samples were sequenced using shotgun metagenomics, ALDEx2 was used for differential abundance analysis of metagenomic data, Kraken and Optivag databases for taxonomic data, and metaphlan3 and Humann3 for functional data. All samples were analysed for HPV using Luminex. Results: A total of 336 women were recruited between 2017–2020. The vaginal microbiota diversity increased with increasing severity of the dysplasia (alpha-diversity measures, Shannon diversity median values: normal =0.771, LSIL= 1.027, HSIL=1.150, and inverse Simpson diversity: normal=1.486, LSIL=1.837, HSIL =2.216). There was a significant difference in diversity when comparing normal to HSIL group (Shannon p < .0001, Inverse Simpson: p < .0001), Figure 1 .The relative abundance of Lactobacilli species decreased with increased severity of dysplasia, especially L crispatus. L iners and G vaginalis were more common among LSIL and the vaginal microbiota of the high grade dysplasia were characterized by mainly non-lactobacilli species, for example Fecalibacterium prausnitzii, Eubacterium rectale, Bacteroides uniformis, Blautia obeum and Rumiinococcus bromii. Conclusion: The vaginal microbiota diversity increased with increasing severity of dysplasia. Further, LSIL and HSIL were characterized by different vaginal microbiota compositions.